2003
DOI: 10.1002/adem.200310075
|View full text |Cite
|
Sign up to set email alerts
|

Achieving a Superplastic Forming Capability through Severe Plastic Deformation

Abstract: Processing by severe plastic deformation (SPD) leads to very significant grain refinement in metallic alloys. Furthermore, if these ultrafine grains are reasonably stable at elevated temperatures, there is a potential for achieving high tensile ductilities, and superplastic elongations, in alloys that are generally not superplastic. In addition, the production of ultrafine grains leads to the occurrence of superplastic flow at strain rates that are significantly faster than in conventional alloys so that proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
38
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 35 publications
10
38
0
Order By: Relevance
“…It was observed that the texture often becomes weak after large torsion deformation, similar to that observed in the PM 6061 Al alloy of this study, and in 6061 Al alloy processed by ECAP [34,43]. Furthermore, the effect of rotation of cube orientation on softening is insignificant, although the Taylor's factor due to the evolution of texture during torsion can decrease [44,45].…”
Section: Hot Deformation Behaviorsupporting
confidence: 66%
See 3 more Smart Citations
“…It was observed that the texture often becomes weak after large torsion deformation, similar to that observed in the PM 6061 Al alloy of this study, and in 6061 Al alloy processed by ECAP [34,43]. Furthermore, the effect of rotation of cube orientation on softening is insignificant, although the Taylor's factor due to the evolution of texture during torsion can decrease [44,45].…”
Section: Hot Deformation Behaviorsupporting
confidence: 66%
“…Also, the higher the homologous temperature, T H (T H = T/T m where T is the temperature test and T m is the melting temperature), and/or the stacking fault energy, the more predominant the dynamic softening processes. On the contrary, the PM 6061 Al alloy treated in this study exhibits softening even though it was reported that the stacking fault energy is lower than that of pure Al [34]. However, softening and hardening have been observed in 6061 Al alloy under torsion deformation at high homologous temperatures of T H = 0.72 and 0.81 [24] and under HPT and ECAP at T H = 0.32 [33,34] whereas the grain size increases with increasing T H .…”
Section: Microhardness Measurementsmentioning
confidence: 54%
See 2 more Smart Citations
“…In broad terms we may term this the classic model for microstructure evolution in highly deformed metals. Xu et al and Langdon [25,26] noted that the classic model would predict a gradually increasing refinement of the microstructure as a result of the continuous introduction of dislocation during the straining process. However, these researchers considered this to be inconsistent with some experimental observations and an alternative model based on an inter-relationship between the formation of subgrain boundaries and shear deformation during ECAP was proposed [25].…”
Section: Introductionmentioning
confidence: 99%